2016
DOI: 10.1097/moo.0000000000000233
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructive techniques in skull base surgery after resection of malignant lesions

Abstract: Resection of skull base tumors, often creating large dural defects that couple with extensive intradural dissection, involving multiple cisterns or the third ventricle, may lead to high-flow cerebrospinal fluid leaks. Reconstruction of the skull base is paramount to achieve an uncomplicated postoperative course. Repair of small dural defects can be reliably achieved using a multilayer grafting technique, which yields a high success rate (>90%). Repair of larger defects associated with a high-flow cerebrospinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 15 publications
0
24
0
1
Order By: Relevance
“…The primary goal of anterior cranial base reconstruction is to separate the intracranial and extracranial compartments, achieving a watertight seal to prevent CSF leaks . This may be achieved via different combinations of free grafts, local flaps, regional flaps, and free tissue transfers . Microvascular reconstruction of the skull base has been well reported in the literature, and a myriad of donor sites have been described to achieve successful skull base reconstruction, although the rectus and radial forearm donor sites are most commonly cited .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary goal of anterior cranial base reconstruction is to separate the intracranial and extracranial compartments, achieving a watertight seal to prevent CSF leaks . This may be achieved via different combinations of free grafts, local flaps, regional flaps, and free tissue transfers . Microvascular reconstruction of the skull base has been well reported in the literature, and a myriad of donor sites have been described to achieve successful skull base reconstruction, although the rectus and radial forearm donor sites are most commonly cited .…”
Section: Discussionmentioning
confidence: 99%
“…As the techniques for expanded endonasal approaches have advanced, so have the development of local and regional flap reconstruction. The majority of skull base defects are successfully reconstructed with a combination of free grafts, local flaps, and regional flaps …”
Section: Introductionmentioning
confidence: 99%
“…There are relatively few studies on sphenoid ORN but it appears to be a life‐threatening condition, with reported survival rates as low as 33% . Several treatment regimen have been described, including conservative management with antibiotherapy or hyperbaric oxygen and more aggressive approaches such as surgical debridement of the necrotic tissues followed by protection of the exposed bone by local or free flaps . However, the extent of ORN may be very variable, and it seems difficult to use a single approach for the management of the various stages of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Preoperative radiological analysis can be helpful in designing the PCF size and guiding the surgeon to properly estimate where incisions are best placed to avoid flaps miscalculation. The PCF might be an option for skull base reconstruction when the nasoseptal flap is not available and postoperative radiotherapy is planned …”
Section: Discussionmentioning
confidence: 99%